The Biomedical Research Hub: a federated platform for patient research data. (22nd November 2021) - Barnes, Craig; Bajracharya, Binam; Cannalte, Matthew; Gowani, Zakir; Haley, Will; Kass-Hout, Taha; Hernandez, Kyle; Ingram, Michael; Juvvala, Hara Prasad; Kuffel, Gina; Martinov, Plamen; Maxwell, J Montgomery; et al.
Abstract: Objective: The objective was to develop and operate a cloud-based federated system for managing, analyzing, and sharing patient data for research purposes, while allowing each resource sharing patient data to operate their component based upon their own governance rules. The federated system is called the Biomedical Research Hub (BRH). Materials and Methods: The BRH is a cloud-based federated system built over a core set of software services called framework services. BRH framework services include authentication and authorization, services for generating and assessing findable, accessible, interoperable, and reusable (FAIR) data, and services for importing and exporting bulk clinical data. The BRH includes data resources providing data operated by different entities and workspaces that can access and analyze data from one or more of the data resources in the BRH. Results: The BRH contains multiple data commons that in aggregate provide access to over 6 PB of research data from over 400 000 research participants. Discussion and conclusion: With the growing acceptance of using public cloud computing platforms for biomedical research, and the growing use of opaque persistent digital identifiers for datasets, data objects, and other entities, there is now a foundation for systems that federate data from multiple independently operated data resources that expose FAIR application programming interfaces, each using a separate data model. Applications can be built that access data from one or more of the data resources.